The Effect of Work Stress and Work Conflict on Employee Performance with Work Motivation as an Intervening Variable at BPJS Ketenagakerjaan Branch Office in Medan Raya - Dian Renita Napitupulu; Isa Indrawan (Yayasan Multidimensi Kreatif, 2024)
BPJS Employment is (Employment Social Security Organizing Agency) is a public program that provides protection for workers to overcome certain socio-economic risks and its implementation uses a social insurance mechanism as a State institution engaged in social insurance. BPJS Ketenagakerjaan, formerly known as PT Jamsostek (Persero), is the implementer of the labor social security law. This study aims to see the effect of Work Stress and Work Conflict on Employee Performance with Work Motivation as an Intervening Variable in Bpjs Employment Branch Office in Medan Raya The results of this study are as follows: Work Conflict has a positive and significant effect on Employee Performance with the original sample value of 0.351 and p values of 0.011. Work Conflict had a positive and significant effect on work motivation with the original sample value of 0.783 and p values of 0.000. Work Motivation had a positive and significant effect on Employee Performance with the original sample value of 0.481 and p values of 0.001. Work Stress had a positive and insignificant effect on Employee Performance with the original sample value of 0.084 and p values of 0.186. Work Stress had a positive and significant effect on Work Motivation with the original sample value of 0.164 and p values of 0.017. Work Conflict has a positive and significant effect on Employee Performance through Work Motivation with the original sample value of 0.377 and p values of 0.001. Work Stress had a positive and insignificant effect on Employee Performance through Work Motivation with the original sample value of 0.079 and p values of 0.050.